Cancer Information-seeking in an Age of COVID-19: Findings from the National Cancer Institute's Cancer Information Service. Issue 1 (2nd January 2021) - Vanderpool, Robin C.; Huang, Grace C.; Mollica, Michelle; Gutierrez, Adrianna I.; Maynard, Candace Deaton
ABSTRACT: Seeking cancer information is recognized as an important, life-saving behavior under normal circumstances. However, given the significant impact of COVID-19 on society, the healthcare system, and individuals and their families, it is important to understand how the pandemic has affected cancer information needs in a crisis context and, in turn, how public health agencies have responded to meeting the information needs of various audiences. Using data from the National Cancer Institute's Cancer Information Service (CIS) – a long-standing, multi-channel resource for trusted cancer information in English and Spanish – this descriptive analysis explored differences in cancer information-seeking among cancer survivors, caregivers, tobacco users, and members of the general public during the onset and continuation of the COVID-19 pandemic (February – September 2020), specifically comparing interactions that involved a discussion of COVID-19 to those that did not. During the study period, COVID-19 discussions were more likely to involve survivors or caregivers compared to tobacco users and the general public. Specific patterns emerged across the four user types and their respective discussions of COVID-19 related to language of service, point of CIS access, stage on the cancer continuum, subject of interaction, cancer site discussed, and referrals provided by the CIS. These results provide insights that may help public health agencies deliver, prioritize, and tailor their messaging and response to specific audiences based on heightened health information needs during a crisis.